Mitochondrial Genome Polymorphisms in the Human Pathogenic Fungus Cryptococcus neoformans - Wang, Yue; Xu, Jianping (Frontiers in Microbiology, 2020)
The Cryptococcus complex consists of at least seven evolutionary divergent lineages and causes ~200,000 fatal human infections each year worldwide. The dominant lineage is Cryptococcus neoformans which consists of three haploid clades VNI, VNII, and VNB, their haploid hybrids, and various diploids derived from intra- and inter-clade mating events. In this study, we analyzed the mitogenomes of 184 strains of C. neoformans. Our analyses revealed that all 184 mitogenomes contained the same 15 protein-coding genes in the same gene order. However, their mitogenome sizes varied between 24,740bp and 31,327bp, primarily due to differences in the number and size of mitochondrial introns. Twelve nucleotide sites within five mitochondrial genes were found to contain introns in at least one of the 184 strains, ranging from 2-7 introns within each mitogenome. The concatenated mitochondrial exon sequences of the 15 protein-coding genes and two rRNA genes showed that VNI, VNII, and VNB strains were separated into distinct clades or sub-clades, largely consistent with results based on nuclear genome SNPs. However, several novel findings were observed. First, one strain of the VNB clade contained mitogenome exon sequences identical to the main VNI mitogenome type but was distant to other VNB mitogenomes. Second, hybrids among clades VNI, VNII, and VNB identified based on their nuclear genome SNPs contained mitogenomes from different clades, with evidence of their mitogenomes inherited from either the MATa or the MATα parents. Third, the eight diploid VNB (C. neoformans) x VNIV (C. deneoformans) hybrids contained recombinant mitogenomes. Fourth, analyses of intron distribution and the paired exon-intron phylogenies for each of the 12 exon-intron pairs suggested frequent gains and losses of mitochondrial introns during the evolution of C. neoformans. The combined mitogenome exon-based phylogeny and intron distributions suggested that clades VNI, VNII and VNB could be further divided into sub-clades. Together, our results revealed a dynamic evolution of mitochondrial genomes in this important human fungal pathogen.